Protein tyrosine kinase but not protein kinase C inhibition blocks receptor induced alveolar macrophage activation - K. Pollock; M. T. Withnall (Mediators of Inflammation)
The selective enzyme inhibitors genistein and Ro 31-8220 were used to assess the importance of protein tyrosine kinase (PTK) and protein kinase C (PKC), respectively, in N-formyl-methionyl-leucyl-phenylalanine (FMLP) induced generation of superoxide anion and thromboxane B2 (TXB2) in guinea-pig alveolar macrophages (AM). Genistein (3–100 μM) dose dependently inhibited FMLP (3 nM) induced superoxide generation in non-primed AM and TXB2 release in non-primed or in lipopolysaccharide (LPS) (10 ng/ml) primed AM to a level > 80% but had litle effect up to 100 μM on phorbol myristate acetate (PMA) (10 nM) induced superoxide release. Ro 31-8220 inhibited PMA induced superoxide generation (IC50 0.21 ± 0.10 μM) but had no effect on or potentiated (at 3 and 10 μM) FMLP responses in non-primed AM. In contrast, when present during LPS priming as well as during FMLP challenge Ro 31-8220 (10 μM) inhibited primed TXB2 release by > 80%. The results indicate that PTK activation is required for the generation of these inflammatory mediators by FMLP in AM. PKC activation appears to be required for LPS priming but not for transducing the FMLP signal; rather, PKC activation may modulate the signal by a negative feedback mechanism.